Can Disturbed Liver Perfusion Revealed in p-CT on the First Day of Acute Pancreatitis Provide Information about the Expected Severity of the Disease?. (14th August 2019) - Pieńkowska, Joanna; Gwoździewicz, Katarzyna; Skrobisz, Katarzyna; Czarnowska-Cubała, Monika; Kozak, Oliwia; Hać, Stanisław; Studniarek, Michał; Szurowska, Edyta
Abstract : Background . The aim of the study was to evaluate the prognostic properties of perfusion parameters of liver parenchyma based on computed tomography (CT) of patients with acute pancreatitis (AP) made on the first day of onset of symptoms, to assess their usefulness in identifying patients with increased risk of the development of severe AP. Methods . 79 patients with clinical symptoms and biochemical criteria indicative of AP underwent perfusion computed tomography (p-CT) within 24 hours after onset of the symptoms. Perfusion parameters in 41 people who developed a severe form of AP were compared with parameters in 38 patients in whom the course of AP was mild. Results . Statistical differences in the liver perfusion parameters between the group of patients with mild and severe AP were shown. The permeability-surface area product was significantly lower, and the hepatic arterial fraction was significantly higher in the group of patients with progression of AP. Conclusions . Based on the results, it seems that p-CT performed on the first day from the onset of AP is a method that, by revealing disturbances in hepatic perfusion, can help in identifying patients with increased risk of the development of severe AP.